Measuring the Commercial Determinants of Health and Disease: A Proposed Framework. (January 2022) - Lee, Kelley; Freudenberg, Nicholas; Zenone, Marco; Smith, Julia; Mialon, Melissa; Marten, Robert; Lima, Joana Madureira; Friel, Sharon; Klein, Daniel Eisenkraft; Crosbie, Eric; Buse, Kent
The commercial determinants of health (CDoH) describe the adverse health effects associated with for-profit actors and their actions. Despite efforts to advance the definition, conceptualization, and empirical analyses of CDoH, the term's practical application to mitigate these effects requires the capacity to measure the influences of specific components of CDoH and the cumulative impacts of CDoH on the health and well-being of specific populations. Building on the Global Burden of Disease Study, we begin by conceptualizing CDoH as risk factor exposures that span agency and structural influences. We identify 6 components of these influences and propose an initial set of indicators and datasets to rank exposures as high, medium, or low. These are combined into a commercial determinants of health index (CDoHi) and illustrated by 3 countries. Although now a proof of concept, comparative analysis of CDoH exposures by population, over time and space, and their associated health outcomes will become possible with further development of indicators and datasets. Expansion of the CDoHi and application to varied populations groups will enable finer targeting of interventions to reduce health harms. The measurement of improvements to health and wellness from such interventions will, in turn, inform overall efforts to address the CDoH.